Cognitive effort during a short-term memory (STM) task in individuals with aphasia. (November 2018) - Kim, Esther S.; Suleman, Salima; Hopper, Tammy
Abstract: People with aphasia (PWA) have been shown to demonstrate limited short-term memory (STM) span capacity, but little is known about the degree of cognitive effort PWA expend when completing STM tasks. For decades, researchers have used task-evoked pupillary responses (TEPRs) to infer cognitive effort; pupil size increases as the difficulty of a task increases. The purpose of this study was to examine TEPRs while PWA and healthy control participants completed a STM picture span task. Sixteen PWA and 16 demographically matched control participants completed paper-based and computer-based versions of a picture span task. Measures of pupil size were collected using an eye-tracking system during the computer-based task. Both PWA and control participants demonstrated increased pupil size as STM demands increased. The two groups did not differ in pupil size across different span levels; however, PWA performed significantly poorer than matched controls in terms of behavioural accuracy scores. This suggests that although PWA exerted similar amounts of effort to control participants as task demands increased, they did not show a corresponding increase in accuracy. These data provide support for the feasibility of using TEPRs to investigate cognitive effort in PWA. In conjunction with behavioural performance measures, measures of cognitive effort may provide a holistic picture of cognitive and linguistic functioning in PWA. Highlights: Pupil size measured as a proxy for cognitive effort during short-term memory task. People with aphasia and controls increased pupil size as task became harder. No differences in pupil size between groups but people with aphasia performed worse. Measuring pupil sizes provide useful information about cognitive effort in aphasia.